Effects of LED light quality on the growth of pepper seedling in plant factory - Liu, Nan; Ji, Fang; Xu, Lijun; He, Dongxian (International Journal of Agricultural and Biological Engineering, 2019)
The extensive environment, especially low temperature and weak lighting in winter and spring, which limits the growth of pepper (Capicum annuum L.) seedlings, the use of plant factory with artificial lighting technology can effectively control the lighting environment to produce high-quality seedlings. In this study, white LED lamps with R:B ratio of 0.7 (L0.7) and 1.5 (L1.5) and red-blue LED lamps with R:B ratio of 3.5 (L3.5) were used to cultivate seedlings of “CAU-24” pepper in the light intensity of 250 μmol/m2·s and photoperiod of 12 h/d, white fluorescent lamps with R:B ratio of 1.7 (F1.7) was used as control. The results showed that plant height, stem diameter, hypocotyl length, biomass accumulation, light energy use efficiency (LUE) and electric energy use efficiency (EUE) of pepper seedling under L1.5 were the highest. After 36 days of sowing, the dry weight of shoot reached 302.8±45.2 mg/plant. Leaf area reached maximum value of 153.5±22.0 cm2 under L0.7. The contents of chlorophyll a, chlorophyll b and total chlorophyll of pepper seedling leaves under all kinds of LED light were greater than F1.7, but there was no significant difference in net photosynthetic rate. The total dry weight with lamp electric power consumption of L1.5 were 3.0 g/(kW·h) which was 1.5, 2, and 3 times greater than that of L3.5, L0.7, and F1.7, respectively. Therefore, compared with fluorescent lamp and other LED lamps, the white LED light quality with R:B ratio of 1.5 is suitable for pepper seedling production in plant factory because of the high LED lighting efficiency, greater LUE and EUE. Keywords: pepper seedlings, LED light quality, R: B ratio, light energy use efficiency (LUE), electric energy use efficiency (EUE) DOI: 10.25165/j.ijabe.20191205.4847 Citation: Liu N, Ji F, Xu L J, He D X. Effects of LED light quality on the growth of pepper seedling in plant factory. Int J Agric & Biol Eng, 2019; 12(5): 44–50.